Synthesis and comparative biological evaluation of bifunctional ligands for radiotherapy applications of 90Y and 177Lu. Issue 5 (1st March 2015) - Chong, Hyun-Soon; Sun, Xiang; Chen, Yunwei; Sin, Inseok; Kang, Chi Soo; Lewis, Michael R.; Liu, Dijie; Ruthengael, Varyanna C.; Zhong, Yongliang; Wu, Ningjie; Song, Hyun A.
Graphical abstract: Abstract: Zevalin® is an antibody-drug conjugate radiolabeled with a cytotoxic radioisotope ( 90 Y) that was approved for radioimmunotherapy (RIT) of B-cell non-Hodgkin's lymphoma. A bifunctional ligand that displays favorable complexation kinetics and in vivo stability is required for effective RIT. New bifunctional ligands 3p- C -DE4TA and 3p- C -NE3TA for potential use in RIT were efficiently prepared by the synthetic route based on regiospecific ring opening of aziridinium ions with prealkylated triaza- or tetraaza-backboned macrocycles. The new bifunctional ligands 3p- C -DE4TA and 3p- C -NE3TA along with the known bimodal ligands 3p- C -NETA and 3p- C -DEPA were comparatively evaluated for potential use in targeted radiotherapy using β-emitting radionuclides 90 Y and 177 Lu. The bifunctional ligands were evaluated for radiolabeling kinetics with 90 Y and 177 Lu, and the corresponding 90 Y or 177 Lu-radiolabeled complexes were studied for in vitro stability in human serum and in vivo biodistribution in mice. The results of the comparative complexation kinetic and stability studies indicate that size of macrocyclic cavity, ligand denticity, and bimodality of donor groups have a substantial impact on complexation of the bifunctional ligands with the radiolanthanides. The new promising bifunctional chelates in the DE4TA and NE3TA series were rapid in binding 90 Y and 177 Lu, and the corresponding 90 Y- and 177 Lu-radiolabeled complexes remained inert in human serum or in mice. The in vitro and in vivo data show that 3p- C -DE4TA and 3p- C -NE3TA are promising bifunctional ligands for targeted radiotherapy applications of 90 Y and 177 Lu.